Sex Tourism and Pre-Exposure Prophylaxis Modality Preferences Among Men Who Have Sex With Men. Issue 4 (13th June 2019) - Brooks, Brandon; Park, Su Hyun; Guilamo-Ramos, Vincent; Schneider, John A.; Harry-Hernandez, Salem; Mgbako, Ofole; Dubin, Samuel; Duncan, Dustin T.
Abstract : Sex tourism among men who have sex with men (MSM) has been associated with increased risk for human immunodeficiency virus (HIV) due to sexually scripted environments characterized by multiple sexual partners, increased availability of alcohol and drugs, and limited availability of HIV-prevention services. The current study examined the knowledge of and likelihood of using different modalities of pre-exposure prophylaxis (PrEP), an important biomedical HIV-prevention strategy, among MSM in Paris who have engaged in sex tourism. A sample of 580 MSM from a highly popular geosocial-networking smartphone application in Paris, France, participated in the survey. Of the 580 MSM, 444 participants reported an HIV-negative status and represent the analytic sample for this study. Approximately 27% reported engaging in sexual tourism. MSM who engaged in sex tourism were more likely to aware of on-demand PrEP and more likely to express interest in using on-demand PrEP (adjusted risk ratio [aRR] = 1.26; 95% confidence interval [CI] = 1.03–1.53, aRR = 1.29; 95% CI = 1.04–1.61, respectively) than MSM who never engaged in sex tourism. Moreover, participants who engaged in sex tourism were more likely to express interest in rectal microbicides or both rectal and penile microbicides (aRR = 1.34; 95% CI = 1.13–1.59, aRR = 1.26; 95% CI = 1.03–1.55, respectively) than participants who had not engaged in sex tourism. With the high likelihood of interest in using alternative forms of PrEP in MSM who engage in sex tourism, this study suggests potential benefits for these alternative forms of PrEP for this specific population and underscores the importance of their continued development.